LITERARY INFLUENCE AND INTERPRETATION OF CREATIVE UNIQUENESS IN UZBEK AND RUSSIAN PROSE - Khamidullayeva, Gavkhar (Журнал иностранных языков и лингвистики, 2023)
The article explores the problem of literary influence on the example of the story and the interpretation of artistic originality in Uzbek and Russian prose, considers the history of the development of literary influence, gives the concept of the genre of the story and lists its compositional features, gives the concept of artistic originality, analyzes the story "Confession" by Leo Tolstoy, the psychology of Leo Tolstoy's creativity in the story "Loneliness" by Shukur Kholmirzaev is analyzed, the artistic originality of the story "Loneliness" by Shukur Kholmirzaev is considered, the philosophical, aesthetic and psychological influence of Leo Tolstoy on Uzbek prose is proved, aspects of Leo Tolstoy's influence on Uzbek literature are determined.